Genetic divergence analysis for morpho-physiological traits, under terminal heat stress, in bread wheat (Triticum aestivum L.) - Kumar, Rajendra; Prasad, Brij Kumar; Singh, Muneendra Kumar; Singh, Gyanendra; Verma, Ajay (Journal of Cereal Research, 2025)
Fifty genotypes of bread wheat were evaluated during rabi crop season, over the two years (2007/08 and 2008/09) at Amar Singh College, Lakhaoti, Bulandshahar, Uttar Pradesh, India, with an objective to work out the genetic divergence for yield and morpho-physiological traits under normal and heat-stress environmental conditions. There was significant differences were observed due to genotypes in respect to all traits under both environments. Fifty genotypes were grouped into 10 diverse clusters under both normal and heat-stress environment. Most of the genotypes (9) were grouped in cluster I and 7 genotypes in cluster I and II under normal and heat- stress conditions. Maximum divergence was observed in cluster II and IX under normal conditions and cluster VI and VIII under heat-stress conditions. Therefore genotypes of these cluster showed more divergence, then genotypes from cluster II, IX, VI and VIII can be used to produce superior hybrids for terminal heat-stress conditions.